2008
DOI: 10.1103/physrevd.77.114014
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon electromagnetic form factors in QCD

Abstract: The nucleon electromagnetic form factors are calculated in light cone QCD sum rules framework using the most general form of the nucleon interpolating current. Using two forms of the distribution amplitudes (DA's), predictions for the form factors are presented and compared with existing experimental data. It is shown that our results describe remarkably well the existing experimental data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
85
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 27 publications
3
85
1
Order By: Relevance
“…It has been noticed that the current interpolating the baryon state is not unique early almost at the beginning when the QCD sum rules were used to the baryon [1,2]. There were many works devoted to this issue [3,4,5,6], particularly for the investigation on the electromagnetic form factors of the nucleon [7,8], which have shown that the choice of the interpolating current may affect the result to some extent. In the previous work [9], we examine the influence due to the choice of the interpolating current for the electromagnetic form factors of the Λ and Σ baryons.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noticed that the current interpolating the baryon state is not unique early almost at the beginning when the QCD sum rules were used to the baryon [1,2]. There were many works devoted to this issue [3,4,5,6], particularly for the investigation on the electromagnetic form factors of the nucleon [7,8], which have shown that the choice of the interpolating current may affect the result to some extent. In the previous work [9], we examine the influence due to the choice of the interpolating current for the electromagnetic form factors of the Λ and Σ baryons.…”
Section: Introductionmentioning
confidence: 99%
“…This method was applied to study the electromagnetic form factors of the nucleon [6,7], and Σ, Λ baryons [8,9], as well as to the study of the rare Λ b → Λl þ l − transition [10]. This rare decay has comprehensively been studied in the framework of the different approaches, such as the relativistic quark model [11], lattice QCD [12], soft collinear effective theory [13], heavy quark effective theory [14], etc.…”
Section: Introductionmentioning
confidence: 99%
“…This matrix element is parametrized in terms of the nucleon DAs and is given in [6,7] (for more details about the nucleon DAs, see also [17]). In order to suppress the higher states and continuum contributions, we perform the Borel transformation over −ðp − qÞ 2 to the expressions of correlation function from the hadronic and the QCD sides, and matching the coefficients of the relevant structures, we get the following sum rules for the form factors:…”
Section: Introductionmentioning
confidence: 99%
“…Following the first formulation of the LCSRs for the electromagnetic form factors in Ref. [9] there have been several studies aimed at finding an optimal nucleon interpolation current [10,[14][15][16] and extending this technique to other elastic or transition form factors of interest. LCSRs for the axial nucleon form factor were presented in [10,15,18], for the scalar form factor in [18] and tensor form factor in [19].…”
Section: Introductionmentioning
confidence: 99%